2014
DOI: 10.1186/s12879-014-0590-4
|View full text |Cite
|
Sign up to set email alerts
|

The burden of nosocomial staphylococcus aureus bloodstream infection in South Korea: a prospective hospital-based nationwide study

Abstract: BackgroundWe estimated the nationwide burden of nosocomial S. aureus bloodstream infection (SA-BSI), a major cause of nosocomial infection, in South Korea.MethodsTo evaluate the nationwide incidence of nosocomial SA-BSI, cases of SA-BSI were prospectively collected from 22 hospitals with over 500 beds over 4?months. Data on patient-days were obtained from a national health insurance database containing the claims data for all healthcare facilities in South Korea. The additional cost of SA-BSI was estimated thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 29 publications
1
23
2
3
Order By: Relevance
“…This is consistent with Chakrakodi et al in the Tertiary Care Indian Hospital [26]. However, this is higher than is previously reported in S. Korea [28], Australia [8] and India [36]. Probable attributes are suggested to be the inappropriate use of antibiotic or inadequate drug dosage during treatment.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with Chakrakodi et al in the Tertiary Care Indian Hospital [26]. However, this is higher than is previously reported in S. Korea [28], Australia [8] and India [36]. Probable attributes are suggested to be the inappropriate use of antibiotic or inadequate drug dosage during treatment.…”
Section: Discussionsupporting
confidence: 91%
“…This may be partly due to the better clinical outcomes in pediatric MRSA bacteremia than in adult cases. Indeed, overall 30-day mortality associated with MRSA bacteremia was 11.1% in this study, which was much lower than that in adult patients (13). A recent prospective cohort study reported a 25.6%, 30-day mortality of invasive MRSA infections in a Korean population with median age 64 years (14).…”
Section: Discussioncontrasting
confidence: 58%
“…The hospital mortality rate between MRSA and MSSA inpatients has long been controversial, and the results in some studies are inconsistent 12,16,17,20,33,40,45,46 . It was reported that patients with MRSA pneumonia infections had a higher mortality rate than those with MSSA (P < 0.001) 13 .…”
Section: Discussionmentioning
confidence: 99%